2017
DOI: 10.26459/hueuni-jns.v126i1b.4261
|View full text |Cite
|
Sign up to set email alerts
|

Development Quality Index Method (Qim) to Assess the Freshness and Shelf Life of Black Tiger Shrimp(penaeus Monodon) Stored at 00c

Abstract: <p>Black tiger shrimps (<em>Penaeus monodon</em>) wereharvested andstored at 0<sup>0</sup>Cfor study. The quality index method (QIM) was developed to evaluate the freshness of black tiger shrimp, and was presented in this study. The terms used to describe all the changes related to the texture, color, and odor are carefully chosen. The development of a QIM scheme included three main steps:A preliminary scheme to evaluate all the changes of attributes related to quality – Final QIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Thus, the controls as well as HM-and AM-treated shrimp were considered adequate for human consumption up to 9, 13, and 12 days, respectively. This period is longer than that reported by Tam et al [20], who reported an average shelf life sensory score of 12 at 8 days of ice storage. Figure 3 compares the evaluation in overall sensory score of P. monodon samples treated with HM or AM solution compared to control samples during ice storage.…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…Thus, the controls as well as HM-and AM-treated shrimp were considered adequate for human consumption up to 9, 13, and 12 days, respectively. This period is longer than that reported by Tam et al [20], who reported an average shelf life sensory score of 12 at 8 days of ice storage. Figure 3 compares the evaluation in overall sensory score of P. monodon samples treated with HM or AM solution compared to control samples during ice storage.…”
Section: Resultsmentioning
confidence: 51%
“…Thus, the controls as well as HM-and AM-treated shrimp were considered adequate for human consumption up to 9, 13, and 12 days, respectively. This period is longer than that reported by Tam et al [20], who reported an average shelf life sensory score of 12 at 8 days of ice storage. Biogenic amines are alkaline organic compounds mainly produced by decarboxylation reactions of free amino acids present in the muscle by the enzyme decarboxylase [20].…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations